Improvement of β-SiC Synthesis Technology on Silicon Substrate - Suchikova, Yana; Kovachov, Sergii; Bohdanov, Ihor; Kozlovskiy, Artem L.; Zdorovets, Maxim V.; Popov, Anatoli I. (MDPI, 2023)
This article presents an enhanced method for synthesizing β-SiC on a silicon substrate, utilizing porous silicon as a buffer layer, followed by thermal carbide formation. This approach ensured strong adhesion of the SiC film to the substrate, facilitating the creation of a hybrid hetero-structure of SiC/por-Si/mono-Si. The surface morphology of the SiC film revealed islands measuring 2–6 μm in diameter, with detected micropores that were 70–80 nm in size. An XRD analysis confirmed the presence of spectra from crystalline silicon and crystalline silicon carbide in cubic symmetry. The observed shift in spectra to the low-frequency zone indicated the formation of nanostructures, correlating with our SEM analysis results. These research outcomes present prospects for the further utilization and optimization of β-SiC synthesis technology for electronic device development. --//-- This is an open-access article: Suchikova, Y.; Kovachov, S.; Bohdanov, I.; Kozlovskiy, A.L.; Zdorovets, M.V.; Popov, A.I. Improvement of β-SiC Synthesis Technology on Silicon Substrate. Technologies 2023, 11, 152. https://doi.org/10.3390/technologies11060152 published under the CC BY 4.0 licence.
The study was supported by the Ministry of Education and Science of Ukraine via Project No. 0122U000129 “The search for optimal conditions for nanostructure synthesis on the surface of A3B5, A2B6 semiconductors and silicon for photonics and solar energy”, Project No. 0121U10942 “Theoretical and methodological bases of system fundamentalization of the future nanomaterials experts training for productive professional activity”, and Project No. 0123U100110 “System of remote and mixed specialized training of future nanoengineers for the development of new dual-purpose nanomaterials”. In addition, the research of A.I.P. and Y.S. was partly supported by COST Action CA20129 “Multiscale irradiation and chemistry driven processes and related technologies” (MultiChem). Y.S. was partly supported by COST Action CA20126—Network for research, innovation, and product development on porous semiconductors and oxides (NETPORE). A.I.P., thanks to the Institute of Solid State Physics, University of Latvia, ISSP UL as the Center of Excellence, is supported through the Framework Program for European Universities, Union Horizon 2020, H2020-WIDESPREAD-01–2016–2017-TeamingPhase2, under Grant Agreement No. 739508, CAMART2 project.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; silicon carbide; silicon; electrochemical etching; solar cells; carbonization; annealing; heterostructures